The characteristics and the satisfaction level of domestic tourists towards the informal sector - Jabil Mapjabil; Badariah Ab Rahman; Noorziah Mohd Salleh; Rosmiza M.Z; Mazdi Marzuki; Mohamad Pirdaus Yusoh; Jeannet Stephen; Datu Razali Datu Eranza; Nor-Ina Kanyo; Christina Andin (Academic Inspired Network (AIN), 2021)
This article examines the characteristics and the level of satisfaction of domestic tourists towards the informal sector at Kota Kinabalu City, Sabah. The study aims is to identify the types, category and characteristics of the informal sector to determine the satisfaction level of the domestic tourist. This study employs a quantitative approach. The method applied was interviews using survey questionnaires, informal interviews, and observation. A total of 90 domestic tourists participated in this study. Finding reveals that there are two types of informal sector preferred by the domestic tourist that is the night market and arcade/ bazaar/shopping complex recorded at the same high score (3.06). Subsequently, the most sold item was the handicrafts and souvenirs with a mean score of 3.04, followed by dried seafood product such as salted terubuk fish, dried shrimp, and anchovies (3.01). More than 80 respondents or 88.9% agreed that most of the informal sector premises offer almost the same product. As for the location of the informal sector scores, the highest mean was the easy access to the destination (3.58) and good facilities and infrastructure (3.32). For the level of satisfaction, the entire items recorded high mean, among others are the variety of products offered (3.79), uniqueness of the purchased product (3.61), and cheap and affordable product (3.36). On the services aspect, two items that scored high mean that is good hospitality (3.71) and the politeness of the salesperson (3.61). Briefly, the findings are important to the policymakers and the interested parties to further explore studies in the field of the informal sector, urban community, and tourism.